Thermal and flammable properties of bamboo pulp fiber/high-density polyethylene composites: Influence of preparation technology, nano calcium carbonate and fiber content. (April 2019) - Wang, Cuicui; Cai, Liping; Shi, Sheldon Q.; Wang, Ge; Cheng, Haitao; Zhang, Shuangbao
Abstract: To investigate the effect of manufacturing method on thermal and flammable performance of CaCO3 impregnation modification (IM) treated bamboo pulp fiber (BPF) composites. The composite was made from HDPE with BPF contents of 30 wt% and 50 wt% by hot press molding (HPMP), extrusion molding (EMP) and injection molding process (IMP). The results showed that the E′, crystallinity index ( CrI ) and heat distortion temperature (HDT) of the composites manufactured by EMP were highest. IM had a slight positive effect on E' and CrI of BPF/HDPE composites. The HDT of composites increased when the fiber content increased, leading to an increase in the heatproof property correspondingly. Compared to the samples manufactured by HPMP and EMP, the samples manufactured by IMP were extremely ignitable and flammable. Nano CaCO3 could improve the flame retardancy performance of samples manufactured by EMP effectively and the fiber content had an effect on the flame retardancy performance of samples, especially the samples treated by nano CaCO3 . The average mass loss rate demonstrated a similar trend to the peak heat release rate for all composites. IM was more effective for EMP to improve the thermal stability and flame retardancy of composites compared with HPMP and IMP. Highlights: The composites were manufactured successfully by HPMP, EMP and IMP. The E′, CrI and HDT of the samples manufactured by EMP were highest. The CrI of IM-BPF/HDPE composite was higher than that of BPF/HDPE composites. The samples manufactured by IMP were extremely ignitable and flammable. IM and fiber content had a different effect on composites manufactured by HPMP, EMP and IMP.